AVAILABILITY OF ARTHROSONOGRAPHY FOR DIAGNOSIS OF SUBCLINIC A L SYNOVITIS IN PATIENTS WITH EARLY GONARTHRITIS (PRELIMINARY DATA) - I. E. Bukina; E S Match; O. V. Pushkova (Научно-практическая ревматология, 2002)
A hs tract. Objective. Analysis of possibilities of arthrosonography of knee joints for ihe diagnosis of synovitis on early stages of gonarthritis. Material and methods. Ultrasound study of knee joints was carried out in 77 patients with gonarthritis of 1-11 Kellgren R-stage, in 12 pts X-ray symptoms of gonarthritis were absent. Study was carried out on ALOKA- 2200 (Japan) using method of two-measured tomography (В-method) with the help of linear sensor with frequency 7.5 MHz in real time. Frontal and posterior (popliteal) surfaces of knee joint were studied using longitudinal and transversal projections in lying position with maximal extension of knee joint. Results. It was found that in the group of joints with clinical synovitis the II radiologic stage of gonarthritis (58,3%) prevailed, and in the group of joints without clinical symptoms of synovitis the 1st radiological stage of gonarthritis (53%) prevailed. In the group of joints with clinical synovitis ultrasound synovitis symptoms were found in 17 joints which is 70.8% of joints with clinical synovitis (24) and 11% of total number of examined joints (154). Fluid in Ihc space of knee joints was localized prevalently over condyle of the Libia (70.8%), in 16.6% fluid was found also in b.suprapatellaris. Enlargement of synovia more than 3 mm prevalently on account of oedema was found in 79.8% whereas in the group of joints without clinical symptoms of synovitis only in 23%. In the group of joints without clinical synovitis subclinical synovitis, i.e. synovitis found in US study was revealed in 34 joints which was 26.1% of the number of joints without clinical synovitis (130) and 22% of total number of examined joints (154). Enlargement of synovia more than 3 mm in this group of joints was found in 23% joints, namely in patients with subclinical synovitis. Decrease of cartilage thickness less than 2 mm was found in great number of joints in the group of joints wilh clinical synovitis as well as in the group og joints without synovitis (95.S% and 91.5% correspondingly). Conclusion. Arthrosonography in early gonarthritis including pre-radiologieal stage is rather informative method of diagnosis of clinical and subclinical synovitis and taking it into consideration allows us to determine optimal therapy of gonarthritis.